Contraction ratio of multifidus and erector spinae muscles in unilateral sacroiliac joint pain: A cross-sectional trial - Omar M. Mabrouk; Khaled E. Ayad; Doaa A. Abdel Hady (Scientific Reports, 2025)
Abstract Sacroiliac joint (SIJ) pain is one of the most prevalent reasons for disability, it affects the contraction ratio of the muscles of the back. Imaging is critical for diagnosing back muscles. The purpose of this study was to look at changes in the muscle contraction ratio of the lumbar multifidus (LM) and erector spinae (ES) in unilateral SIJ pain. This research included 60 individuals (30 with unilateral SIJ pain and 30 healthy people (who served as matching controls). The contraction ratio of back muscles such as ES and LM was assessed using real-time ultrasonography, and the results were compared between the affected and non-affected sides in patients with unilateral SIJ pain, and healthy participants as well. In the study group, the contraction ratio of ES and LM muscles on the non-affected side was significantly higher than on the affected side (p < 0.05). as well as a significant increase in contraction ratio of the ipsilateral side (affected matched control side) LM of the healthy group compared with that of the non-affected side of the study group (p < 0.001), while there was no significant difference in contraction ratio of the contralateral (unaffected matched control side) ES of the healthy group compared with that of the non-affected side of the study group. The results of this trial demonstrate that patients with unilateral SIJ pain exhibited a substantially lower muscle contraction ratio in the ES and LM of the affected side than the non-affected side in the study group, as well as a significant increase in the contraction ratio of the ES and MF on the ipsilateral side of the control group compared with that of the study group. However, there was no significant change in the contraction ratio of the contralateral ES in healthy individuals compared to the non-affected side of the study group. The findings of the study may help in designing an appropriate exercise program to deal with patients with SIJ pain.